Retinal Nerve Fiber Layer as The Preferred Objective Measure in Differentiating Pseudopapilledema with True Papilledema: A Systematic Review: Oral Presentation - Observational Study - General practitioner - Lourisa Ruth Eldenia; Rona Ali Badjrai; Lazuardiah Anandi; Fierda Ovita Azhari; Erika Anggraini; Brigitta Marcia Bidihardja; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Distinguishing pseudopapilledema from true papilledema may generate confusion for some cases. Regardless of the subjective judgment on clinical examination alone, objective measurement for confirmation of diagnosis might be costly, operator-dependent, invasive, or not readily available. This study aims to evaluate whether retinal nerve fiber layer (RNFL) could be the reliable and efficient objective measure to ascertain the diagnosis. Methods : Literatures were obtained by comprehensive searching on PubMed, ProQuest, Google Scholar, and Cochrane between 2012 - 2023. Last search was March 26, 2023. Non-english study, animal study, review articles, case studies, and editorial letters were excluded. We included studies with available full-text containing both groups of papilledema and pseudopapilledema. The result was presented according to Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guideline. Results : A total of 615 participants were included from 8 different studies all comprising a group of papilledema and pseudopapilledema with or without optic disc drusen (ODD). Studies resulted in good accuracy on RNFL in differentiating pseudopapilledema with papilledema as the area under curve ranging from 0,78 to 0,91. However, specificity and sensitivity were varied between 65-100% and 33-91% respectively. Lower accuracy was found when pseudopapilledema only includes patients with ODD or papilledema was narrowed to mild papilledema. Conclusion : RNFL is a useful objective measure with favorable accuracy in differentiating pseudopapilledema with papilledema especially in acute settings or whenever operator-dependent examination is not obtainable